Impact of Acute Intermittent Exercise on Natural Killer Cells in Breast Cancer Survivors. (September 2015) - Evans, Elizabeth S.; Hackney, A. C.; McMurray, Robert G.; Randell, Scott H.; Muss, Hyman B.; Deal, Allison M.; Battaglini, Claudio L.
Background. Current research examining the effect of exercise on immune responses in cancer survivors is limited. Objective. The aim of this pilot study was to examine the effect of 1 bout of intermittent exercise on natural killer (NK) cell numbers in breast cancer survivors. Methods. A total of 9 women with stage I to III invasive breast cancer who were 3 to 6 months posttreatment and 9 sedentary women without a history of cancer completed 10 three-minute intervals of aerobic exercise on the cycle ergometer at 60% of VO2peak (peak oxygen uptake). Whole blood samples were taken pre-exercise, immediately postexercise, and at 2 hours and 24 hours postexercise. NK cell counts were assessed using flow cytometry. Results. In both groups, NK cell counts significantly increased immediately postexercise compared with pre-exercise ( P = .004-.008) and returned to near pre-exercise levels during recovery ( P = .129-.547). Absolute NK cell counts were significantly lower in breast cancer survivors immediately postexercise when compared with controls ( P = .046). Conclusions. The breast cancer survivor group exhibited NK cell responses to 30 minutes of moderate-intensity intermittent aerobic exercise that were comparable with that in the group of physically similar women without a history of cancer. Immune changes related to cancer treatments may be related to the lower absolute NK cell counts observed in the breast cancer survivor group. Although the results of this study are preliminary in nature, they suggest that this type of exercise does not disrupt this aspect of innate immunity in recent breast cancer survivors, thereby supporting current exercise recommendations for this population.